Public media and public theology: At loggerheads or partners in complexity? - Botma, Gabriël (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Media criticism, both from inside the journalism and media studies fraternity and outside, such as theology, often depart from reductionist normative functionalist and critical political economy perspectives. Examples from the former perspective include complaints from theologians that the media set the agenda, also relating to matters of religion, and that the content the media provide does not contribute to a healthy, moral and peaceful society. Media researchers who adopt critical perspectives often argue in turn that the media are tied to elite capitalist interests and values and contribute to the marginalisation and suppression of the disenfranchised in the deeply unequal post-apartheid South African society.